PROFESIONALITAS GURU MI PROGRAM DUAL MODE SYSTEM FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA DALAM PEMBELAJARAN AQIDAH - Sangkot Sirait (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2013)
This work is a report of research from Dual Mode System’s universtity students at Tarbiyah Faculty in teaching the subject of Islamic Theology. The research aims to understand the teacher’s competence in teaching Islamic Theology. The results of the research indicates that all teachers, generelly, have tougt well according to their teaching plans. But from metodological aspects especially material development, they do not not have competence in their work. The process of teaching is still dominated by lecturing; there is no connection other disciplines, and the teachers do not have interconnetive and integrative perspectives when teaching. The doctrinal approach is dominan.The main problem exists in teaching Islamic Theology is reducting of material, for examples, when they teach the subject of belief in Prophets and Books. Explaining of Prophets is only by explaining the Prophet of Muhammad. And so does for Books. When they teach Belief in Books, their explaination is only to the Qur’an. Of course, the problems of teaching is caused by competence of teachers who do not have philosopical perspectives when teaching, particularly,teaching religion like Islamic Theology. For example, they can not differenciate between universalism and particularism, and it is difficult to differenciate between Prophets and Muhammad.